USE OF PLATELET-RICH FIBRIN (PRF) IN MAXILLOFACIAL BONE GRAFTS - Henriques, Maria Eduarda Batista; Rocha, José Rodrigo Mega; Freitas, Gabriel Lemos; Rosa, Joana de Lima Santa; Bonfim, Paulo Rogério Castro; Vicente, Lorena Mell Silveira Pimentel; Lira, Rayane Cássia Batista; Silva, Dreyce Myllena; Silva, Diego dos Santos (Seven Editora, 2026)
Tooth extraction triggers a healing process in the socket, involving the formation of a clot rich in growth factors. However, the alveolar ridge undergoes bone atrophy, making future rehabilitations, such as dental implant placement, more difficult. Platelet-Rich Fibrin (PRF) has emerged as a regenerative technique widely used in implant dentistry, especially for bone grafting procedures. It is a three-dimensional matrix rich in cytokines and platelet- and leukocyte-derived growth factors that promotes angiogenesis, cell proliferation, and accelerated healing, with a lower risk of adverse effects compared to PRP. Despite PRF’s clinical effectiveness, there is still a lack of well-defined protocols, which hinders its standardization and optimization. The absence of consensus regarding dosage, application technique, and appropriate timing represents a challenge to achieving consistent outcomes. This study aims to discuss the clinical use of PRF in bone grafts in the orofacial region, analyzing its effectiveness in bone regeneration, acceleration of the healing process, and reduction of postoperative complications. It is an integrative literature review based on studies published between 2020 and 2024, using databases such as LILACS and SciELO. The results indicate that PRF is effective in promoting bone stability and regeneration in post-extraction sockets and is also beneficial for patients with comorbidities, such as diabetes or anticoagulant use, due to its hemostatic effect. When combined with biomaterials, PRF has shown promising outcomes, but further studies are urgently needed to standardize protocols and ensure improved long-term clinical results.